PPAR γ agonist, pioglitazone, suppresses melanoma cancer in mice by inhibiting TLR4 signaling - Nasim Dana; Golnaz Vaseghi; shaghayegh haghjooy javanmard (Frontiers Media S.A., 2019)
Background:  Although previous studies demonstrated an anticancer effect for the ligands of peroxisome proliferator-activated receptor gamma (PPARγ) through activation of its anti-inflammatory responses, nevertheless the anti-tumor mechanism of PPARγ has not been intensively investigated. One of the molecules involved in cancer progression is toll-like receptor 4 (TLR4). Methods: B16F10 melanoma cells were cultured with or without LPS for 24 hr. The cells were subcutaneously injected to two groups of C57BL/6 mice. After the development of palpable tumors each group of animals were divide to four sub-groups and received pioglitazone in different dose ranges (0,10,50,100 mg/kg/day) for 10 days. At the end of the study, the expression of Tlr4, Myd-88, Nf-kb1 genes was evaluated by qRT-PCR in different groups in mice tumor. The TLR-4 protein expression was evaluated by IHC. TNF-α level in mice tumor and serum were measured by ELISA kits. Tumor volume was measured with Vernier calipers. Results: We observed that activation of PPARγ by its agonist, pioglitazone, reduces tumor volume, Tlr-4, Myd-88, Nf-kb1 mRNA expression, TLR4 protein expression and TNF-α production in melanoma tumor especially in groups that were injected with LPS -stimulated cells. Moreover, treatment of melanoma cells with pioglitazone showed that the inhibitory effects of pioglitazone on LPS-induced inflammatory responses were TLR4 dependent. Conclusions: The results indicate that pioglitazone, a PPARγ agonist, has a beneficial protective effect against melanoma via interfering with the TLR4-dependent signaling pathways.